THE NATURAL ENVIRONMENT AS A LEARNING SOURCE FOR SCIENCE: IMPLEMENTATION STRATEGY - Widodo Setiyo Wibowo (Journal of Science Education Research, 2019)
Science is closely related to nature, so the natural environment is one of the most important sources of learning both as means and an object. The particular study aimed to discuss the strategy of using and implementing the natural environment as a learning source for science in junior high schools. The results found out that the use of the natural environment as a learning source for science can be pursued through fieldwork, bringing the environment into the classroom, or also making the school science parks. Using the natural environment as a learning source for science requires careful preparation and planning from the teacher. The learning implementation performed in 3 main stages; preparation, implementation, and follow-up. Through the proper implementation of these stages, various benefits achieved either for students or teachers.